Penerapan Metode Tutor Sebaya untuk Meningkatkan Minat Belajar Peserta Didik pada Pembelajaran Matematika - Nanda Nur Rahmawati; Suhartono Suhartono (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This study aimed to enhance the mathematics learning interest of 10th-grade students at SMA Negeri 21 Surabaya through the implementation of peer tutoring with a Problem-Based Learning model in statistics. The background of this research is the low learning interest of students, particularly in mathematics. This study employs a Classroom Action Research (CAR) method, consisting of two cycles. Data was collected through observation, interviews, and tests. The results of the study showed that the application of peer tutoring in the Problem-Based Learning model can improve the learning interest and critical thinking skills of 10th-grade students at SMA Negeri 21 Surabaya in statistics. This can be seen from the improvement in observation results, interviews, and test scores. Students' learning activities and critical thinking skills increased with a higher average percentage in the second cycle compared to the first cycle. The peer tutoring method with the Problem-Based Learning model enables students to learn from and help each other, thus increasing their motivation and engagement in learning. Additionally, this method helps students develop their interpersonal and communication skills.